Peran Kebijakan Deviden (DPR) Memediasi Earning Per Share (EPS) Dan Return On Equity (ROE) Terhadap Return Saham Perusahaan Manufaktur Di Bursa Efek Indonesia - Faradila Meirisa (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
This study aims to analyze the factors that influence stock returns. In addition, this study also aims toexamine the influence of dividend policy mediation variables on the relationship between Earning Per Share and ReturnOn Equity on Stock Returns. To test these variables, the researcher used the PLS-SEM (Partial Least Square) analysistool and 70 manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 – 2022. The results ofthis study indicate that there is a significant positive effect of Earning Per Share on Stock Returns, Return On Equityhas a positive and significant effect on stock returns, and there is a significant positive effect on earnings per share andreturn on equity variables on stock returns mediated by dividend payout policy.